Measurement and modeling of excess pore-water pressure in warm saturated frozen soil based on dynamic loading effect - Hu Zhang; Jintao Hu; Zheng Li; Bo Zheng; Huijun Jin; Yaling Chou; Hongchun Li; Ming Lu; Suiqiao Yang (Alexandria Engineering Journal)
Measuring pore-water pressure (PWP) in frozen soils poses significant challenges in geotechnical testing experiments, and understanding PWP is crucial for unraveling the mechanism of frost heave generation in cold regions. This paper aims to clarify the development pattern of PWP in frozen soil through laboratory tests, specifically focusing on excess PWP generated under dynamic loading. Seven sets of triaxial tests were conducted to investigate the variations in excess PWP and deformation influenced by temperature, dynamic stress amplitude, and dry density. The results reveal that excess PWP in warm saturated frozen soil undergoes two stages: pore pressure increase and dissipation. The change of external factors mainly affects the peak value of excess PWP and the change rate of excess PWP. Unlike unfrozen soil, excess PWP has a small dissipation rate after the peak and may remain dynamically stable in the later stage of loading. In addition, two empirical models of excess PWP applicable to saturated frozen soils were proposed based on the developmental patterns of excess PWP in frozen soils, and the feasibility was validated using the results obtained from laboratory tests. The model is of great significance for predicting the development of excess PWP in frozen soil under dynamic load.